Penerapan Metode K – Means Clustering untuk Menentukan Kepuasan Mahasiswa terhadap Fasilitas Sarana dan Prasarana Kampus di STMIK Kaputama Binjai - Dicha Mutia Dhani; Relita Buaton; I Gusti Prahmana (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Technological advancements in the era of globalization demand improvements in the quality of academic services and educational facilities in institutions. STMIK Kaputama is committed to creating a conducive academic environment by providing optimal facilities. This study aims to determine student satisfaction with campus facilities using the K-Means Clustering method. Data were obtained from recapitulated survey reports and questionnaires filled out by students in 2024. The K-Means Clustering method was chosen for its ability to group students based on their similar preferences for campus facilities. The results show that, in general, students are fairly satisfied, though their preferences for specific facilities vary. These findings can be used to make recommendations for the improvement and development of campus facilities, help STMIK Kaputama allocate resources more efficiently, and plan strategies to enhance the quality of facilities to meet student expectations.